The comprehension of Italian relative clauses in poor readers and in children with Specific Language Impairment. Issue 1 (16th February 2017) - Arosio, Fabrizio; Panzeri, Francesca; Molteni, Bruna; Magazù, Santina; Guasti, Maria Teresa
Abstract : Children with Specific Language Impairment (SLI) and children with Developmental Dyslexia (DD) have problems comprehending relative clauses (RCs) and find object RCs more difficult than subject RCs, as do typically developing children. Few studies have compared these groups directly, leaving it unclear whether the problems observed in children with DD are similar to those described in SLI. Work with typically developing children has shown that the comprehension of passive RCs is less challenging than that of object RCs. It is argued that this asymmetry depends on intervention effects as modelized in a Relativized Minimality framework. Since movement is challenging for children with SLI and those with DD, examining and comparing their comprehension of object RCs and passive RCs can broaden our understanding of their language deficits. In fact, both structures involve movement, but the moved element and the movement configuration are different. In our study we investigated the comprehension of subject RCs, object RCs and passive RCs in 12 Italian monolingual children with SLI (mean age: 7;6), 13 Italian monolingual children with DD (mean age: 10;7) and 50 typically developing controls matched for age, grammar and vocabulary. Results from a picture selection task show that: (i) subject RCs are unproblematic for all children; (ii) object RCs are challenging for children with SLI, children with DD and younger typically developing controls; (iii) passive RCs are better understood than object RCs in all groups, but still problematic for children with SLI and younger typically developing controls. Our data show that intervention effects are found in children with SLI and children with DD and that those with SLI have a deficit in transferring thematic roles to moved elements. Our results point out that some of the children with DD have a mild grammatical deficit that was undetected or escaped standardized tests.